Działania nauczycieli języków obcych a założenia dydaktyki wielojęzyczności - Kucharczyk, Radosław (Neofilolog, 2022)
The article presents the result of our own research conducted among foreign language teachers. The aim of the study was to diagnose the extent to which the surveyed teachers implement the assumptions of multilingualism didactics, the focus of which is the ability to make positive inter-language transfer. Making such a transfer requires the student to develop - with the support of the teacher - a range of strategies based on the resources of their own linguistic repertoire, which is not possible without the ability to manage their own learning process and the emotions that accompany it, and to adopt a reflective attitude based on their previously acquired foreign language learning experience.